Evaluation of Integrated Nutrient Management Practices on Growth, Yield and Economics of Green Chilli cv Pusa Jwala (Capsicum annuum L.) - Leela Rani, P.; Balaswamy, K.; Rao, A. Ramachandra; Masthan, S. C. (International Journal of Bio-resource and Stress Management, 2023)
The present study was carried out during 2007 and 2008 rabi season at Agricultural Research Institute, Rajendranagar, Hyderabad, Telangana state, India. with 9 treatment combinations (Recommended dose of inorganic fertilizer (200-60-80 kg NPK ha-1), 150% of RDNF, 200% of RDNF, 250% of RDNF, Complete organic N through FYM (25%) and neem cake (25%) as basal and vermicompost as top dressing (50%), 50% organic+50% RDNF, 75% organic+75% RDNF, 100% organic+100% RDNF, 125% organic+125% RDNF) in randomize block design with 3 replications. Combined application of 150 kg N ha-1 along with 10 t FYM and 0.5 t neem cake ha-1 showed significant increase in plant height (59, 58 cm), canopy spread (40.7, 42.1 cm), number of branches plant-1 (23, 23), number of fruits plant-1 (194,164), yield plant-1 (410, 315 g) and total green chilli yield of 13306 and 10550 kg ha-1 respectively. But number of fruits plant-1, yield plant-1 and total yield ha-1 were on par with combined application of 100 and 125% organic manures and inorganic fertilizers each, respectively. However in terms of benefit cost ratio combined application of 150 kg N ha-1 along with 10 t FYM and 0.5 t neem cake was economical with highest net returns (` 79923 and ` 52369 ha-1) and B:C (2.5 and 1.99). Significantly the lowest growth, yield attributes and fruit yield (1924 and 3577 kg ha-1) of green chilli with negative net returns (` 45063 and ` 28537 ha-1) and lower B C (0.3 and 0.56) was noticed in complete organic manure application.